Enhancing Perovskite Thin Films with Butylammonium Iodide-Lead-Tetrahydrofuran: Surface Healing and 2D Formation in Annealing-Free Single-Crystal Films for Solar Cell Applications - Farhad Azad; Thidarat Supasai; Annafi Ado Yaro; Kay Thi Soe; Non Thongprong; Ekkaphop Ketsombun; Navaphun Kayunkid; Ratchadaporn Supruangnet; Narong Chanlek; Patrick Chapon; Nopporn Rujisamphan (ACS Materials Letters, 2024)
We demonstrate a functional method to achieve surface passivation and construct a two-dimensional (2D) layer on a three-dimensional (3D) perovskite, eliminating the need for subsequent annealing steps. A key process is the integration of a single methylammonium lead iodide (MAPbI3) crystal with butylammonium iodide (BAI) in tetrahydrofuran. Density functional theory calculations reveal that the synergy between BA+ cations and Pb–I octahedral structures enables the formation of a distinct 2D layered framework. MA+ and BA+ exhibit adsorption energies of −5.519 and −5.925 eV, respectively, at MA vacancies on the perovskite surface. This finding indicates that BAI passivation induces surface-healing effects, increasing surface and device stability. The I– components of BAI also replace imperfections at the perovskite interface, affording considerably reduced deep-level anomalies and mitigating nonradiative recombination. This theoretical perspective is supported experimentally via X-ray photoelectron spectroscopy and glow discharge optical emission spectroscopy. BAI passivation and 2D-BA2PbI4 capping lowers work functions for 3D perovskite surfaces, registering at approximately 0.158 and 0.173 eV, respectively, which are lower than those of the control 3D film. Within the 2D/3D perovskite configuration, 2D-BA2PbI4 capping considerably increases the open-circuit voltage in solar cells. In comparison, devices with BAI-enhanced interfaces show improved durability with promise for solar cell applications.
Keywords: Perovskite Materials and Applications; Conducting polymers and applications; Quantum Dots Synthesis And Properties